MiR-17-5p Inhibits TXNIP/NLRP3 Inflammasome Pathway and Suppresses Pancreatic β-Cell Pyroptosis in Diabetic Mice - Sijun Liu (Frontiers Media S.A., 2021)
Objective: Diabetes mellitus is a chronic progressive inflammatory metabolic disease with pancreatic β-cells dysfunction. The present study aimed to investigate whether miR-17-5p plays a protective effect on pancreatic β-cells function in diabetes mellitus (DM) mice and dissect the underlying mechanism.Methods: C57BL/6J mice were randomly divided into control, DM, DM + Lentivirus negative control (LV-NC), and DM + Lenti-OE™ miR-17-5p (LV-miR-17-5) groups. DM was established by feeding a high-fat diet and intraperitoneal injection with streptozotocin (STZ) in mice. Blood glucose and glucose tolerance in circulation were measured. Meanwhile, the activation of nod-like receptor protein 3 (NLRP3) inflammasome, pancreas pyroptosis, and the expression of miR-17-5p and thioredoxin-interacting protein (TXNIP) were detected in the pancreas of DM mice. Pancreatic β-cell line INS-1 subjected to different concentrations of glucose was used in in vitro experiments.Results: Compared with control mice, glucose tolerance deficit, elevated blood glucose level, and decreased pancreatic islet size, were presented in DM mice, which was associated with a downregulation of miR-17-5p. Importantly, exogenous miR-17-5p alleviated pancreas injury, and consequently improved glucose tolerance and decreased blood glucose in DM mice. In vitro experiments showed that high glucose decreased miR-17-5p expression and impaired insulin secretion in INS-1 cells. Mechanistically, miR-17-5p inhibited the expression of TXNIP and NLRP3 inflammasome activation, and thus decreased pancreatic β-cell pyroptosis.Conclusion: Our results demonstrated that miR-17-5p improves glucose tolerance, and pancreatic β-cell function and inhibits TXNIP/NLRP3 inflammasome pathway-related pyroptosis in DM mice.